UPAYA MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN MELALUI BIMBINGAN BERKELANJUTAN DI SD NEGERI 1 PURWODADI - Winarti, Lilik Endah (Universitas PGRI Adi Buana Surabaya, 2019)
Some teachers at Purwodadi 1 Elementary School adopted another person's Learning Implementation Plan. This researcher knows when conducting academic supervision (supervision of class visits) to the target schools. These problems have a big influence on the implementation of the learning process. Under these circumstances, researchers as school advisers strive to provide ongoing guidance to teachers in compiling a Learning Implementation Plan in full in accordance with the demands on process standards and assessment standards that are part of the national education standard. Based on the research conducted, the following results can be obtained: (1) Continuous guidance can increase the motivation of the teacher in compiling a Learning Implementation Plan completely. The teacher shows the seriousness in understanding and compiling the Learning Implementation Plan especially after getting guidance on the development / preparation of the Learning Implementation Plan from the researcher. This information researchers obtained from the results of observations when conducting interviews and guidance development / preparation of Learning Implementation Plans to teachers; and (2) Continuous guidance can improve teacher competence in preparing Learning Implementation Plans. It can be proven from the observation / observation that shows that there is an increase in teacher competency in compiling the Learning Implementation Plan from cycle to cycle. In the first cycle the average value of the components of the Learning Implementation Plan was 69% and in the second cycle 83%. So, there was a 14% increase from the first cycle